20. SURVEY ON THE RELATIONSHIP BETWEEN TONGUE CHARACTERISTICS AND TRADITIONAL MEDICINE BODY CONSTITUTION TYPES IN STUDENTS (Tạp chí Y học Cộng đồng, 2024)
Objectives: To evaluate the relationship between tongue characteristics and Traditional Medicine body constitution types in healthy volunteers from the Faculty of Traditional Medicine (TM) in the University of Medicine and Pharmacy at Ho Chi Minh City (UMP).Subjects and research methods: The cross-sectional study of 424 TM students at the UMP was conducted from January to April 2024. Primary outcome variables included body constitution (BC) types (via the Vietnamese version of the Constitution in Chinese Medicine Questionnaire), and tongue characteristics (extracted by ZMT-1A machine). Chi-square tests were used to analyze relationships between BC types and tongue characteristics.Results: Distribution analysis showed that the Neutral constitution was the most common (64.6%). BC types related with tongue body characteristics include color, size, fissures, and papillae (p
Keywords: Tongue diagnosis; tongue characteristics; body constitution types; CCMQ